Genetic predisposition to long telomeres is associated with increased mortality after melanoma: A study of 2101 melanoma patients from hospital clinics and the general population. (7th May 2021) - Ismail, Hafsa; Helby, Jens; Hölmich, Lisbet R.; H. Chakera, Annette; Bastholt, Lars; Klyver, Helle; Sjøgren, Pia; Schmidt, Henrik; Schöllhammer, Liv; Nordestgaard, Børge G.; Bojesen, Stig E.
Abstract: Whether there is an association between measured and genetically predicted telomere length and melanoma mortality is unclear. We tested the hypothesis that measured and genetically predicted telomere length is associated with mortality after a melanoma diagnosis. We followed 2, 101 patients with melanoma from hospital clinics and the general population for risk of death for up to 26 years. All had telomere length measured in DNA from leukocytes, and 2052 of these were genotyped for the three single nucleotide polymorphisms rs7726159 ( TERT ), rs1317082 ( TERC ), and rs2487999 ( OBFC1 ); all three genotypes are associated with telomere length and combined into an allele count from 0 to 6. For each telomere‐lengthening allele, the hazard ratios (HRs) for mortality in the age‐adjusted and multivariable‐adjusted Cox analysis were 1.12 (95% confidence interval: 1.02–1.23) and 1.11 (1.01–1.23). However, for each standard deviation increase in measured telomere length, HR for mortality was 0.97 (0.88–1.08). In conclusion, in more than 2000 melanoma patients from hospital clinics and from the general population, genetically predicted long telomeres were associated with increased mortality, but measured leukocyte telomere length was not.